Pedagogical System Approach to Search, Development and Support of Gifted and Talented Students - Galustov, Ambartsum Robertovich; Glukhov, Vladimir Stepanovich; Galustov, Robert Ambartsumovich (International Review of Management and Marketing, 2016)
In the article the problems of system approach to search, development and supports of gifted and talented students in pedagogical higher education institutions are considered. The problems restraining effective work on search, development and support of gifted children and youth in Russia and the main solutions of these problems are defined on the example of work with children and youth in Armavir State Pedagogical Academy. It is shown that system approach to search, development and support of talented children and youth has to be based on such basic principles, as system, integrity, hierarchy, structure and plurality. As a result of the conducted research it is proved that pedagogical system approach allows to reveal, develop and provide most effectively a targeted support of search, development and support of gifted youth. One of the effective mechanisms of identification, development and support of gifted and talented students in pedagogical higher education institutions is involvement of students in student design, technological and technical scientific centers, bureaus, design scientific groups, etc. The main activities of students in scientific units in a higher educational institution can be mechatronics, robotics, multimedia modeling of technologies, mechanisms, as well as studying modern measuring technological sensors and devices. The organization and management of identification process, development and targeted support of student intellectual and creative activity are carried out by means of consolidation of scientific and pedagogical staff of a higher education institution for the solution of this problem. Keywords: pedagogical system approach, development, support of gifted, talented youth, consolidation of scientific and pedagogical staff JEL Classifications: J24; I21; Z13